Roman pictures - Lubbock, Percy, 1879-1965 (Salt Lake City, UT : Project Gutenberg, 2023)
"Roman Pictures" by Percy Lubbock is a fictional work likely written in the early 20th century. The narrative unfolds through the eyes of a young protagonist, who becomes entangled in the vibrant life of Rome and its intriguing characters, notably a man named Deering, who embodies the essence of a worldly and cultured life. The story promises a rich exploration of themes such as identity, friendship, and the contrast between romantic ideals and reality. The opening of the book introduces the reader to a picturesque scene at the Fountain of the Tortoises in Rome, where the narrator reflects on his solitude and the enchanting environment that surrounds him. He unexpectedly encounters Deering, an acquaintance from England, who exudes confidence and a deeper connection to the city's culture. As they converse, the narrator grapples with feelings of inadequacy and admiration towards Deering's more refined nature. This meeting marks the beginning of the narrator's journey through the complexities of Roman life, as he seeks to transcend his previous romantic notions and embrace a more authentic understanding of the city and its inhabitants. Through Deering, the narrator aims to step into a world that is both alluring and unexpectedly challenging, setting the stage for an exploration of self and society within Rome's vibrant tapestry. (This is an automatically generated summary.)
Release date is 2023-10-06
Chuck Greif and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Rome (Italy) -- Fiction; British -- Italy -- Rome -- Fiction